Kondisi optimal PCR untuk mendeteksi gen FimH isolat klinis Escherichia coli penyebab infeksi saluran kemih - Prisela Zharaswati; Ni Nyoman Sri Budayanti; Ni Nengah Dwi Fatmawati (Intisari Sains Medis, 2019)
Background: Urinary tract infection is one of the most common infectious diseases and the second most common infection after respiratory tract infection. Bacteria are the most common cause of urinary tract infections in more than 95% of cases. Escherichia coli is the most common bacteria that found in 80-90% of cases of urinary tract infection. The critical virulence factor of Escherichia coli is the type 1 fimbriae with the adhesion subunit, fimH, plays an essential role in the pathogenesis of urinary tract infection.Aim: The research aims to obtain the optimal condition of PCR in detecting the fimH gene with modification of annealing temperature in the PCR process.Method: This study used a sample of fimH DNA genes from clinical isolates of E. coli causing UTI. The second PCR used an annealing temperature of 57°C and a third PCR using an annealing temperature of 64°C. The electrophoresis results are then viewed with an ultraviolet transilluminator. Result: The optimization finding showed that the annealing temperature of 52 °C, 57 ° C, and 64°C could detect the fimH gene where the higher the temperature used by Tm, the less the specificity produced.Conclusion: The optimum annealing temperature of PCR to identify the fimH gene from E.coli causes the UTI is in the temperature of 64°C with better specificity than of 52°C. The annealing temperature of 64°C indicates the lowest specificity.